1986
DOI: 10.3171/jns.1986.65.1.0019
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of epilepsy after ventricular shunting procedures

Abstract: One hundred eighty of 207 consecutive patients with ventricular shunts were studied to determine the incidence of post-shunt epilepsy. Of these 17 (9.4%) developed seizures. The incidence fell from 15.2% in children younger than 1 year to 6.9% in patients over 50 years of age, but age was not statistically significant. Of patients with a parietal ventricular catheterization site only 6.6% had convulsions, in contrast to 54.5% of those with a frontal locus. The incidence of seizures rose with multiple ventricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(26 citation statements)
references
References 6 publications
1
22
1
1
Order By: Relevance
“…The risk of seizure as a result of shunt placement itself, however, is controversial. 6,48,74 Some work has suggested that frontal rather than parietal bur-hole placement was associated with increased incidence of seizure, 16 though these data have not been corroborated by other studies. 63,79,88 Thus perioperative seizures related to shunt placement are not an independent complication of surgery but warrant discussion given that they are common and can be problematic.…”
Section: Perioperative Epilepsymentioning
confidence: 94%
“…The risk of seizure as a result of shunt placement itself, however, is controversial. 6,48,74 Some work has suggested that frontal rather than parietal bur-hole placement was associated with increased incidence of seizure, 16 though these data have not been corroborated by other studies. 63,79,88 Thus perioperative seizures related to shunt placement are not an independent complication of surgery but warrant discussion given that they are common and can be problematic.…”
Section: Perioperative Epilepsymentioning
confidence: 94%
“…4,8,15) In the present case, irritation of the brain parenchyma associated with previous hemorrhage or insertion of the ventricular catheter, and further worsened by a migrated prechamber, can be considered as an epileptogenic factor, in addition to the possible re-existent elevat-…”
Section: Discussionmentioning
confidence: 99%
“…Ventricular shunting procedures are associated with a widely varying incidence, ranging from 2% to 47%. 6,8,9) Infection of the system was associated with a higher risk. 8,9) Therefore, surgeons should avoid infection of the system to reduce the risk.…”
Section: Postoperative Early Seizuresmentioning
confidence: 99%